Nasser's Blessed Movement : Egypt's Free Officers and the July revolution - Gordon, Joel (Joel S.) (Studies in Middle Eastern history (New York, N.Y.), 1992)
This book examines a key period in the formation of modern Egypt, the early years of military rule following the coup of 1952. The Free Officers Corp, a group of junior officers, overthrew Egypt's parliamentary regime in July 1952 and over the next few years consolidated their rule, brutually supressing alternative political movements. Gamal Abdel Nasser, one of the young officers, emerged as the leader of the military junta and launched an ambitious programme for economic development, making Egypt a leader in Arab, African, and non-aligned politics, as well as a model for political mobilization and national development throughout the Third World. Focusing on the goals, programmes, successes, and failures of the young regime, Gordon provides the most comprehensive account of the Egyptian revolution to date. Besides bringing to light newly opened American and British sources on the period, Gordon's book is also informed by interviews he conducted with a number of actors and observers of the events.